2007
DOI: 10.1101/lm.524907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid forgetting of social transmission of food preferences in aged rats: Relationship to hippocampal CREB activation

Abstract: A major characteristic of age-related changes in memory in rodents is an increase in the rate of forgetting of new information, even when tests given soon after training reveal intact memory. Interference with CREB functions similarly results in rapid decay of memory. Using quantitative immunocytochemistry, the present experiment examined the number of CREB-and pCREB-immunoreactive neurons in three regions of the dorsal and ventral hippocampus (dentate gyrus, CA3, and CA1) as a function of age and training. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 89 publications
(105 reference statements)
7
39
0
Order By: Relevance
“…Importantly, the present findings may bridge the concepts of cellular consolidation developed by McGaugh (2) and extensively studied over the years by his group and by many others (18,22,23), including ours (6,17,19,29,39), and that of systems consolidation, originally posited by Squire and his collaborators (40-44). Squire and his associates produced substantial evidence that there is a consolidation process that may last for weeks in rodents and for years in humans (40).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Importantly, the present findings may bridge the concepts of cellular consolidation developed by McGaugh (2) and extensively studied over the years by his group and by many others (18,22,23), including ours (6,17,19,29,39), and that of systems consolidation, originally posited by Squire and his collaborators (40-44). Squire and his associates produced substantial evidence that there is a consolidation process that may last for weeks in rodents and for years in humans (40).…”
Section: Discussionmentioning
confidence: 62%
“…In addition, deficits in BDNF and in ERK signaling are associated to memory impairment in the aging brain (35,36). Age-related memory impairments have often been characterized in terms of rapid forgetting, in which aged animals have relatively comparable learning and memory on tests performed 24-48 h after training, but poor LTM retention at later times (6). Unraveling the molecular mechanisms involved in memory persistence may help to understand and treat the deficits in memory storage associated with normal and pathological aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, old (24-month-old) Wistar rats typically demonstrate reduced social recognition in juvenile compared to young (3-month-old) rats (Prediger et al, 2006). Similarly, memory retention in the STFP test with test delays exceeding 24 h was impaired in old (32-month-old) rats compared to young (3-month-old) subjects (Countryman and Gold, 2007). Interestingly, the memory impairments in the STFP test in aged rats were associated with decreased pCREB, notably in the ventral hippocampus (see also Section 4.2.1) (Countryman and Gold, 2007).…”
Section: Factors That Influence Social Memorymentioning
confidence: 99%
“…It has been suggested that the neocortical cholinergic system, particularly the orbitofrontal component 19 may be more important than the hippocampal cholinergic system for social transmission. Social transmission has even been shown to track memory impairment in aged rats, probably mediated by decreased CREB (cAMP-response element-binding protein) transmission in the aged hippocampus 7 .…”
mentioning
confidence: 99%